Predictors of Tuition Worth: Psychological Sense of Community, Institutional Integrity, and Student Thriving. Issue 3 (27th May 2017) - Conn, Steven M.
ABSTRACT: Using hierarchical multiple regression analysis, this study examined the factors that contribute to the variation in students' subjective perceptions of the value of their tuition dollars. This study utilized data on 6, 322 undergraduate students from 11 institutions in the Council for Christian Colleges & Universities (CCCU) who completed the Thriving Quotient questionnaire. The results revealed that psychological sense of community (β = .321) was the strongest predictor of students' perception that their tuition was a worthwhile investment. Financial difficulty was the second strongest predictor (β = –.245), and students' perception of institutional integrity was the third strongest (β = .161). These findings indicate that helping students develop a sense of community on campus and perceive that their institutions are meeting the expectations created during the admissions process are important elements of helping students appreciate the value of their tuition. Further discussion on the theoretical and practical applications of the findings are included.